2021
DOI: 10.1182/bloodadvances.2020003848
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-year outcomes with CAR T cells (ZUMA-1) vs salvage chemotherapy in refractory large B-cell lymphoma

Abstract: The SCHOLAR-1 international retrospective study highlighted poor clinical outcomes and survival among patients with refractory large B-cell lymphoma (LBCL) treated with conventional chemotherapy. Axicabtagene ciloleucel (axi-cel), an autologous anti-CD19 chimeric antigen receptor T-cell therapy, demonstrated durable responses in patients with refractory LBCL in the pivotal phase 1/2 ZUMA-1 study (NCT02348216). Here, we compared SCHOLAR-1 with the 2 year outcomes of ZUMA-1. Prior to comparison of clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 29 publications
5
51
1
1
Order By: Relevance
“…To our knowledge, only one other study has compared a CAR-T cell therapy vs historical control treatment as 3L+ treatment of r/r DLBCL using patient-level data. Specifically, Neelapu et al 28 compared the 2-year clinical outcomes with conventional chemotherapy vs with axi-cel using data from the SCHOLAR-1 and ZUMA-1 (Study Evaluating the Safety and Efficacy of KTE-C19 in Adult Participants With Refractory Aggressive Non-Hodgkin Lymphoma) studies, respectively, using propensity scoring to create similar patient populations. The study reported that axi-cel was associated with a higher ORR and CR rate vs conventional chemotherapy (ORR and CR, 83% and 54% in ZUMA-1 vs 34% and 12% in SCHOLAR-1, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one other study has compared a CAR-T cell therapy vs historical control treatment as 3L+ treatment of r/r DLBCL using patient-level data. Specifically, Neelapu et al 28 compared the 2-year clinical outcomes with conventional chemotherapy vs with axi-cel using data from the SCHOLAR-1 and ZUMA-1 (Study Evaluating the Safety and Efficacy of KTE-C19 in Adult Participants With Refractory Aggressive Non-Hodgkin Lymphoma) studies, respectively, using propensity scoring to create similar patient populations. The study reported that axi-cel was associated with a higher ORR and CR rate vs conventional chemotherapy (ORR and CR, 83% and 54% in ZUMA-1 vs 34% and 12% in SCHOLAR-1, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A major breakthrough ensued with the development of second-generation CARs, which integrate a co-stimulatory endodomain (usually CD28 or 4-1BB) upstream of CD3z (Brentjens et al, 2007;Imai et al, 2004). Beginning in 2010, second-generation CD19-CARs emerged as the most efficacious adoptive T cell therapy to date, mediating potent and long-lasting responses in high-grade B cell lymphoma in adults (Abramson et al, 2017;Kochenderfer et al, 2010Kochenderfer et al, , 2012Neelapu et al, 2017;Schuster et al, 2017;Turtle et al, 2016b) and in B cell acute lymphoblastic leukemia (B-ALL) in both children and adults who are refractory to all stan-dard therapies (Brentjens et al, 2011;Gardner et al, 2017;Grupp et al, 2013;Lee et al, 2015;Maude et al, 2015Maude et al, , 2018Turtle et al, 2016a).…”
Section: T Cell Therapies For Cancermentioning
confidence: 99%
“…Further, scFv affinity and/or CAR density could be optimized to target tumors that express heterogeneous levels of antigen or to limit CARmediated toxicity (as discussed in more detail below). Significant toxicities have been observed in patients treated with T cells expressing CD19 CARs, including cytokine release syndrome (CRS), whereby CAR T cell anti-tumor activity results in high levels of secreted IL-6, IL-1, and sepsis-like symptoms (Giavridis et al, 2018;Neelapu et al, 2017;Norelli et al, 2018), as well as immune effector cell-associated neurotoxicity syndrome (ICANS), which is associated with endothelial cell dysfunction at the blood-brain barrier induced by a hyperinflammatory milieu (Gust et al, 2017). Although these toxicities have resulted in serious or even fatal complications, lowering CAR T cell dose, and treatment with steroid therapy or antibodies blocking IL-6R (i.e., tocilizumab) has been highly effective.…”
Section: T Cell Therapies For Cancermentioning
confidence: 99%
“…In DLBCL, the novel‐agent arm in all four studies enrolled patients during more recent intervals than the SCHOLAR‐1 dataset 3,4,11,12 . All four studies adjusted for key potential confounders using individual patient data.…”
Section: Figurementioning
confidence: 99%